PENERAPAN MODEL PEMBELAJARAN KOORPERATIF TIPE NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Rahmawati, Rahmawati; Baidowi, Baidowi; Suntoko, Iwan (Mandalika Mathematics and Educations Journal, 2025)
This research is motivated by the low mathematics learning outcomes of students in class VIII K of SMPN 1 Mataram. This research aims to improve mathematics learning outcomes in class VIII K of SMPN 1 Mataram for the 2023/2024 academic year using the Numbered Head Together (NHT) type cooperative learning model. This type of research is classroom action research which is divided into 3 cycles and each cycle consists of 2 meetings. Data collection techniques use tests and observations. The research results shows that there is an increase in mathematics learning outcomes of students in class VIII K using the NHT type cooperative learning model. In the first cycle masery learning is 38%. In the second cycle masery learning increased to 57%. In the third cycle masery learning increased to 81%. Based on this description, it can be concluded that the implementation of the Numbered Head Together (NHT) cooperative learning model can improve mathematics learning outcomes of students in class VIII K students of SMPN 1 Mataram for the 2023/2024 academic year.